Linguistic Approaches in Teaching Arabic Language at Madrasah Aliyah Negeri 1 Mamuju, West Sulawesi - Marwati; Limpo, Marwah; Alfikri Rausen Aditya (Universitas Islam Negeri Alauddin, 2023)
This research is entitled Linguistik Approach in Teaching Arabic at Madrasah Aliyah Negeri 1 Mamuju, West Sulawesi (Strengthening the Arabic Literature Study Program). The type of research used is qualitative research. The nature of this research is exploratory. The theory used in this research is Kanneth L. Pike's tagmemic theory and the scope of the discussion is focused on the study of Arabic language learning syntax. The results of this research have found that Madrasah Aliyah Negeri 1 Mamuju, West Sulawesi still uses traditional methods in teaching Arabic. So the need for renewal to gain effectiveness in learning Arabic using a linguistik approach